PERAN ETIKA KRISTEN DALAM PENDIDIKAN AGAMA KRISTEN MEMBENTUK KARAKTER MORAL PESERTA DIDIK - Ferdi Arison Ga Djami; Derfen Irens Zakarias Sesfao; Orpa Letuna; Elfi Boimau (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Christian Religious Education plays a strategic role in shaping the moral character of students amid increasingly complex moral challenges. Christian ethics, as an integral part of the Christian faith, serves as a value foundation that guides students’ attitudes, behaviors, and life decisions. This study aims to examine the role of Christian ethics in Christian Religious Education in shaping students’ moral character. The method used in this study is a literature review by analyzing various theological, educational, and relevant research sources related to Christian ethics and character formation. The findings indicate that the integration of Christian ethical values, such as love, honesty, responsibility, and justice, into the learning process of Christian Religious Education significantly contributes to the development of students’ moral character. In addition, the example set by Christian Religious Education teachers and the contextual application of Christian ethical values in students’ daily lives are important factors in the success of character education. Therefore, Christian Religious Education grounded in Christian ethics can serve as an effective means of forming faithful, ethical, and morally responsible students.